If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -53 + 12X = 115 Solving -53 + 12X = 115 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + 12X = 115 + 53 Combine like terms: -53 + 53 = 0 0 + 12X = 115 + 53 12X = 115 + 53 Combine like terms: 115 + 53 = 168 12X = 168 Divide each side by '12'. X = 14 Simplifying X = 14
| 9x-2[x+4]=34 | | Ln(4x-7)=ln(x+5) | | -63=-27-3X | | y+5.8=1.34 | | x+(-12)=112 | | (h^3-2h)+(3h^2+4h)-2h^3= | | 4y=6x-4 | | 100-5p=-20+7p | | 127=-11x-71 | | -8(y+1)+1=-8y-6 | | x(31-5-x)=10-3x | | 147=63+6x | | 5x-7=2x+7 | | 10m-17m-25m+21m+m=16 | | -5x+23=32 | | 7(x-1)=5(x-15) | | ln(8x-7)=2 | | 8x+44=100 | | 10x+(16y+6)=180 | | 2z+3z= | | -5(x+4)+6=-3(2x+2)+x | | 4x^2+256=y | | 2(3x-51)-x=10-3x | | 22=-14+2x | | -7h-5=-4-4h | | 4z+9z-2z=10 | | 7(x-2)=(x+3) | | 4x+8=20-7x | | 2y+15=3y-1 | | -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 |